Opportunities and hope: time for action - Łabno, Anna (A thousand years of Poland's presence among the elite of European states, 2026)
Professor Anna Łabno opened her closing remarks by reminding the audience that the Polish president's competencies — though limited — carry real significance. As an example, she cited the presidential veto and the right to submit motions to the Constitutional Tribunal, noting that in 2009 the political forces currently in power sought to eliminate those prerogatives entirely. Only public resistance prevented those changes from taking effect. For Professor Łabno, this episode serves as proof that organized civic action can successfully block unfavorable constitutional changes.The central message of her address was a call to move from diagnosing threats to taking concrete, organized action. Professor Łabno urged conference participants to establish an informal structure that would allow them to develop effective ways of engaging society — particularly younger generations, who in her view are not disengaged by choice but rather lack adequate educational and civic support. She stressed that the proposed activity should be social rather than political in nature, since politics is a concept that many Poles find off-putting.In her closing remarks, Professor Łabno offered an important caution: excessive pessimism in public communication can produce the opposite of the intended effect, discouraging people from engaging with shared concerns. She expressed hope that the conference would mark the beginning of lasting collaboration, and appealed to those present to maintain an attitude full of hope — because only in that way can one effectively reach a broader audience and build a movement capable of bringing about real change.